The Digital Dilemma: Perspectives From Otolaryngology Residency Applicants on Social Media. (September 2022) - Patro, Ankita; Landeen, Kelly C.; Stevens, Madelyn N.; Cass, Nathan D.; Haynes, David S.
Objective: To evaluate the impact of otolaryngology programs' social media on residency candidates in the 2020 to 2021 application cycle. Methods: An anonymous survey was distributed via Otomatch, Headmirror, and word of mouth to otolaryngology residency applicants in the 2021 Match. Survey items included demographics, social media usage, and impact of programs' social media on applicant perception and ranking. Descriptive statistics were performed, and responses based on demographic variables were compared using Fisher's exact and Mann-Whitney U tests. Results: Of 64 included respondents, nearly all (61/64, 95%) used Facebook, Instagram, and/or Twitter for personal and/or professional purposes. Applicants (59/64, 92%) most commonly researched otolaryngology residency programs on Instagram (55/59, 93%) and Twitter (36/59, 61%), with younger ( P  = .023) and female ( P  = .043) applicants being more likely to engage with programs on Instagram. Program accounts were most helpful in showcasing program culture (50/59, 85%) and highlighting its location (34/59, 58%). Nearly one third (19/59, 32%) reported that social media impacted their rank list. Age, gender, reapplication, home program status, or time taken off before and/or during medical school did not significantly influence social media's usefulness in the application cycle. Conclusion: Social media platforms like Instagram and Twitter are frequently used by applicants to assess otolaryngology residency programs. Programs' social media accounts effectively demonstrate program culture and affect applicants' rank lists. As social media usage continues to rise in the medical community, these findings can help otolaryngology residency programs craft a beneficial online presence that aids in recruitment, networking, and education.